Analysis of Students’ Misconceptions on Solving Algebraic Contextual Problem - Faoza Saaroh; Tian Abdul Aziz; Dwi Antari Wijayanti (Risenologi, 2021)
Students misconceptions in solving contextual algebraic problems is still often found in this educational world. This study aims to describe the forms of student’s misconceptions in solving algebraic contextual problems and explain the causes of these misconceptions. The approach in this research is a qualitative approach, that is library research where the data used are secondary data. This research uses literature review data collection techniques. The number of articles used as data sources is 19 articles related to topics in research with algebraic contextual items taken from 5 articles to be displayed in the results section of the study. Data analysis used descriptive analysis method by describing the intentions and comparing several research articles. The results showed several forms related to non-systematic errors, namely concept errors or students’ misconceptions in solving algebraic contextual problems, namely the occurrence of misconceptions within the scope of algebraic arithmetic operations, understanding the meaning of variables, simplifying, or operating algebraic expressions, and interpreting contextual problems into algebraic mathematical form. The misconception occurs in students with low and moderate mathematical abilities where the cause of this phenomenon is due to the occurrence of errors in the learning process by educators in which students are less accustomed to solving contextual problems or open-ended questions. Therefore, it is hoped that educators can determine the learning model appropriately in fixing the problem of contextual algebraic misconceptions and further researchers can find new learning models that affect this problem.